PENGARUH PEMBERIAN PUPUK BOKASHI FESES SAPI SUMBA ONGOLE TERHADAP PRODUKTIVITAS INDIGOFERA ZOLLINGERIANA - Tomy Umbu Jaiwu Anakoda; Marselinus Hambakodu (Universitas Kristen Wira Wacana Sumba, 2022)
The aims of the experiment was to demine the effect of giving bokashi fertilizer Sumba Ongole cattle feces on the productivity of the Indigofera zollingeriana. This experiment used a completely randomized design (CRD) with 5 treatments with 4 replications consisting of: P0=without bokashi fertilizer/planting hole, P1=200 grams/planting hole, P2=500 grams/planting hole, P3=800 grams/planting hole, and P4=1000 grams/planting hole. Variables observed in this experiment consisted of plant height, total of leaves, stem diameter, fresh matter production, and dry matter production. The results showed that the application of bokashi fertilizer Sumba Ongole cattle had not significant effect (P<0.05), on plant height, number of leaves, fresh matter production, and dry matter production, but it has not significant effect on stem diameter. The application of bokashi fertilizer from Sumba Ongole cattle feces the level of 500 grams/planting hole could increased plant height, total of leaves, fresh matter production, and dry matter production of Indigofera zollingeriana.